2005
DOI: 10.1099/mic.0.27444-0
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in the DNA- and cNMP-binding domains of the homologue of the cAMP receptor protein (CRP) in Mycobacterium bovis BCG: implications for the inactivation of a global regulator and strain attenuation

Abstract: The genome of Mycobacterium tuberculosis H37Rv includes a homologue of the CRP/FNR (cAMP receptor protein/fumarate and nitrate reduction regulator) family of transcription regulators encoded by Rv3676. Sequencing of the orthologous gene from attenuated Mycobacterium bovis Bacille Calmette-Gué rin (BCG) strains revealed point mutations that affect the putative DNA-binding and cNMP-binding domains of the encoded protein. These mutations are not present in the published sequences of the Rv3676 orthologues in M. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 39 publications
3
51
1
Order By: Relevance
“…Only Rv0867c (rpfA) and Rv1552 ( frdA) are predicted by both their study and the present study to be members of the putative CRP Mt regulon (65). The regulation of rpfA by CRP Mt has also recently been experimentally confirmed (54).…”
Section: Discussionmentioning
confidence: 58%
“…Only Rv0867c (rpfA) and Rv1552 ( frdA) are predicted by both their study and the present study to be members of the putative CRP Mt regulon (65). The regulation of rpfA by CRP Mt has also recently been experimentally confirmed (54).…”
Section: Discussionmentioning
confidence: 58%
“…A point mutation in the CRP-FNR-like regulator (Mb3700) alters global gene expression and attenuates the strain. This mutation has been traced back to post-1924 and affects the HTH domain of the regulatory protein (Spreadbury et al, 2005). This mutation is likely to be present in many of the daughter derivative strains that were passaged independently by different laboratories prior to the development of a seed-stock in the 1960s.…”
Section: Vaccinesmentioning
confidence: 99%
“…Each of the Wbl family of proteins contains four invariant cysteine residues, which are believed to be involved in binding a [4Fe-4S] cluster (Jakimowicz et al, 2005). The functional importance of this cluster is emphasized by the observation that none of the four whiD alleles carrying mutations at these cysteine residues was able to complement the whiD mutant phenotype in S. coelicolor (Jakimowicz et al, 2005).It has recently been reported that the M. tuberculosis gene Rv3676 encoding a CRP-FNR family protein (hereafter referred to as CRP M ) is defective in the vaccine strain Mycobacterium bovis BCG (Spreadbury et al, 2005). Moreover, an M. tuberculosis mutant lacking an intact Rv3676 gene is attenuated for virulence and shows reduced expression of several mycobacterial genes including resuscitation promoting factor, rpfA (Rickman et al, 2005).…”
mentioning
confidence: 99%
“…It has recently been reported that the M. tuberculosis gene Rv3676 encoding a CRP-FNR family protein (hereafter referred to as CRP M ) is defective in the vaccine strain Mycobacterium bovis BCG (Spreadbury et al, 2005). Moreover, an M. tuberculosis mutant lacking an intact Rv3676 gene is attenuated for virulence and shows reduced expression of several mycobacterial genes including resuscitation promoting factor, rpfA (Rickman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%